The involvement of soluble epoxide hydrolase in the development of cardiovascular diseases through epoxyeicosatrienoic acids - Jiang, Shan; Han, Siyi; Wang, Dao Wen (Frontiers in Pharmacology, 2024)
Arachidonic acid (AA) has three main metabolic pathways: the cycloxygenases (COXs) pathway, the lipoxygenases (LOXs) pathway, and the cytochrome P450s (CYPs) pathway. AA produces epoxyeicosatrienoic acids (EETs) through the CYPs pathway. EETs are very unstable in vivo and can be degraded in seconds to minutes.EETs have multiple degradation pathways, but are mainly degraded in the presence of soluble epoxide hydrolase (sEH). sEH is an enzyme of bifunctional nature, and current research focuses on the activity of its C-terminal epoxide hydrolase (sEH-H), which hydrolyzes the EETs to the corresponding inactive or low activity diol.Previous studies have reported that EETs have cardiovascular protective effects, and the activity of sEH-H plays a role by degrading EETs and inhibiting their protective effects. The activity of sEH-H plays a different role in different cells, such as inhibiting endothelial cell proliferation and migration, but promoting vascular smooth muscle cell proliferation and migration. Therefore, it is of interest whether the activity of sEH-H is involved in the initiation and progression of cardiovascular diseases by affecting the function of different cells through EETs.